2000
DOI: 10.1046/j.1523-536x.2000.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected Cochrane Systematic Reviews: Oral Misoprostol for Induction of Labour with a Viable Fetus

Abstract: A substantive amendment to this systematic review was vaginal prostaglandins (relative risk 1.29, 95% confidence interval 0.90-1.86). Different doses (100 micro-last made on 6 November 1998. Cochrane reviews are regularly checked and updated if necessary.grams three hourly and 200 micrograms six hourly) were used in the two trials that compared oral with vaginal misoprostol. The caesarean section rate was ABSTRACT 21.8% in the oral misoprostol group compared with 13.5% for vaginal misoprostol (relative risk 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Misoprostol, an inexpensive and stable prostaglandin E1 analogue, has been shown to stimulate uterine contractility in early pregnancy 2 and at term. 3 Administered orally or vaginally, it is effective for inducing abortion 4,5 and labour, [6][7][8] though it poses certain risks. 9,10 Administration of this drug on a wide scale at the community level to prevent and treat postpartum haemorrhage is of major public health importance.…”
Section: Introductionmentioning
confidence: 99%
“…Misoprostol, an inexpensive and stable prostaglandin E1 analogue, has been shown to stimulate uterine contractility in early pregnancy 2 and at term. 3 Administered orally or vaginally, it is effective for inducing abortion 4,5 and labour, [6][7][8] though it poses certain risks. 9,10 Administration of this drug on a wide scale at the community level to prevent and treat postpartum haemorrhage is of major public health importance.…”
Section: Introductionmentioning
confidence: 99%
“…Replacing dinoprostone with misoprostol would allow considerable cost savings. Although misoprostol can be administered vaginally, orally or rectally, the vaginal route appears, at present, to offer the most benefits in terms of efficacy and minimising side effects 4–6 . Danielian et al 7 found that 50 μg of misoprostol was more effective than dinoprostone gel and had a similar side effect profile, but others have demonstrated that a dosing regimen of 50 μg or higher is associated with an increased incidence of uterine contraction abnormalities 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturers have acknowledged the role of doctors in prescribing an approved pharmaceutical product for use outside its approved indication 12 . The Cochrane Review 13 on the topic remains inconclusive because widely varying dosage regimens have been used and the studies to date have been far too small to address the issue of safety. We have emphasised the dangers of misoprostol, particularly in larger dosages, and the need for large studies to confirm safety.…”
Section: Introductionmentioning
confidence: 99%